LIGHTWEIGHT DESIGN OF STATOR FOR LARGE CAPACITY PERMANENT MAGNET GENERATOR SET - MA DengHui; YU ShenBo; ZHAI FengChen; DOU RuTong (Jixie qiangdu)
The stator stiffness and strength are systematically analyzed according to the characteristics of stator structure and load condition in order to achieve the goal of stator lightweight design of large-capacity outer rotor permanent magnet wind turbine generator set. The stress and deformation of the stator are obtained,and the optimal area of the stator are determined. Under the condition of ensuring the stiffness and strength of the stator,the initial topology optimization of stator is designed by variable density method. On this basis,the dimension parameters that have great influence on the stator mass,stiffness and strength are determined by sensitivity analysis and optimized by response surface method. After optimization,the maximum stress and strain of the stator are in the allowable range. The mass of stator is reduced by 1 199 kg,which means that it is 11. 25% lighter than the original stator. Therefore,the optimization method studied in this paper works well for the lightweight target.